Predatory Activity of Myxobacteria Corallococcus exiguus against Soil Inhabiting Bacteria - Meliah, Siti; Nurindahsari, Miranti; Purnaningsih, Ismu (Universitas Atma Jaya Yogyakarta, 2023)
Prokaryotic micropredators, including myxobacteria, shape the structure of the community in the soil as they prey on other microorganisms. Their unique behavior in nature has raised the interest in exploiting these bacterial groups to combat the threatening antibiotic resistance. The objective of this study is to assay the antibacterial activity of Corallococcus exiguus, a member of myxobacteria, based on their predation ability against soil inhabiting bacteria. A total of 17 soil bacteria from different taxa were preyed upon three C. exiguus isolates on TPM buffer agar medium. Based on the predation assay, all the three isolates actively killed all the Gram-negative Alphaproteobacteria and Betaproteobacteria members used in this study. Protease producing assay using casein as substrate revealed that these isolates were able to break down the protein with lytic index up to 1.33 ± 0.10. Their ethyl acetate extracts slightly inhibited the growth of one selected Gram-positive bacterium. Hydrolytic enzyme and secondary metabolite produced by C. exiguus are considered to play an important role in their predation activity.